1981
DOI: 10.1063/1.328527
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect in quasiharmonic infrared bands of stressed polymers

Abstract: The effect of temperature on vibrational frequency shifts in mechanically stressed polymer chains is analyzed. A single chain is modeled as a weakly coupled, one-dimensional series of anharmonic diatomic oscillators. The anharmonic potential is described as a perturbation of the harmonic potential with cubic and quartic terms. Expressions are derived for the dominant, quasiharmonic contribution to the temperature-dependent frequency shifting coefficient a c , and distinctions are drawn between the vibrational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…If during heating these stresses are reduced, the bands should shift to higher frequencies. The analysis of the data (Bretzlaff, 1981(Bretzlaff, , 1983Vettegren, 1992Vettegren, , 2009Bronnikov, 1996) shows that the "red" shift of the absorption bands under external mechanical stresses in highly oriented polypropylene is less than 3 cm -1 even at scission strain (Bretzlaff, 1981(Bretzlaff, , 1983. In our case the observed bands shift is several times higher ( Figure 10).…”
Section: Journal Of Materials Science Researchsupporting
confidence: 49%
See 2 more Smart Citations
“…If during heating these stresses are reduced, the bands should shift to higher frequencies. The analysis of the data (Bretzlaff, 1981(Bretzlaff, , 1983Vettegren, 1992Vettegren, , 2009Bronnikov, 1996) shows that the "red" shift of the absorption bands under external mechanical stresses in highly oriented polypropylene is less than 3 cm -1 even at scission strain (Bretzlaff, 1981(Bretzlaff, , 1983. In our case the observed bands shift is several times higher ( Figure 10).…”
Section: Journal Of Materials Science Researchsupporting
confidence: 49%
“…Let's investigate frequency position temperature dependences. It is known that the Δν T frequency shift during temperature increase from T 1 to T 2 , in other polymers, (Bretzlaff, 1981(Bretzlaff, , 1983Vettegren, 1992Vettegren, , 2009Bronnikov, 1996) can be written as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average stress application rates for Figure 4 I. An interpretation of these shifts in terms of their "mixing" and "anharmonic" contributions is given in ref 16.…”
Section: Resultsmentioning
confidence: 98%
“…This is because semicrystalline polymers such as polyethylene exhibit a marked deviation from linear viscoelastic behavior even at small strains [1][2][3][4][5] . It has been identified that plastic deformation, such as dislocation, microvoid formation, and the slippage of crystallites, can arise from any applied deformation [6][7][8] and that anharmonic elastic response can be caused by mechanical and thermal excitations 9,10) . To fully describe the stressrelaxation behavior of semicrystalline polymer solids, it is necessary to consider both contributions from plastic deformation and anharmonic response.…”
Section: Introductionmentioning
confidence: 99%